Aspects of confinement from QCD correlation functions - Fischer, Christian S.; Maas, Axel Torsten; Pawlowski, Jan M. (Arxiv, 2008)
We discuss the properties of ghost and gluon propagators in Landau gauge Yang-Mills theory and their relation to the confinement problem. In general two types of infrared behavior of these functions are allowed from their functional equations: scaling and decoupling. Both solutions show positivity violations in the gluon propagator and lead to a confining Polyakov loop potential. However, only the scaling solution agrees with the Kugo-Ojima confinement scenario and the related formulation of a physical Hilbert space of Yang-Mills theory. Our numerical results for the gluon dressing function agree almost pointwise with the lattice results at all physical momenta.
Gesehen am 05.12.2017